Contribution of Culturally Responsive Digital Learning Based on Indigenous Values in Students’ Mental Health - Henri; Junaeda, St.; Nur'aini, Tiara; Pasaribu, Deasy (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2026)
Social media and digital technologies have a profound influence on adolescents’ mental health. Consequently, educational practices need to integrate technological innovation with cultural values to support students’ psychological well-being. This study aims to examine the contribution of Culturally Responsive Digital Learning (CRDL), grounded in indigenous values, to strengthening the mental health resilience of students at SMAN 1 Jeneponto in the era of social media. Amid increasing psychological pressures associated with rapid digital transformation, educational approaches that integrate technology with local cultural values have become increasingly relevant and necessary. The analytical framework of this study is based on Geneva Gay’s theory of Culturally Responsive Pedagogy, which emphasizes that students’ cultural identities and local wisdom constitute valuable resources that can function as protective factors and sources of emotional resilience. This study employed a descriptive qualitative approach to explore digital learning practices rooted in indigenous cultural values. Data validity was ensured through source triangulation, method triangulation, and member checking to enhance the credibility and trustworthiness of the findings. The results indicate that CRDL contributes significantly to students’ mental health resilience through five key dimensions. First, project-based digital learning activities, such as the creation of vlogs and podcasts, enhance students’ self-confidence by encouraging them to become active and empowered content creators rather than passive consumers. Second, the integration of cultural norms and etiquette fosters responsible and ethical behavior in navigating social media environments. Third, reinforcing culturally grounded conceptions of self-worth helps students reduce their dependence on superficial forms of digital validation, such as likes, comments, and follower counts. Fourth, learning activities centered on family interaction strengthen emotional bonds and reaffirm the family’s role as a primary source of support and psychological security. Fifth, educational practices that promote cultural diversity and mutual respect have proven effective in preventing cyberbullying and fostering positive social interactions in digital spaces. Abstrak: Media sosial dan teknologi digital memengaruhi kesehatan mental remaja. Oleh karena itu, pembelajaran perlu mengintegrasikan teknologi dan nilai budaya. Penelitian ini bertujuan mengkaji kontribusi Culturally Responsive Digital Learning (CRDL) berbasis Indigenous Values dalam menguatkan mental health resilience (resiliensi kesehatan mental) siswa SMAN 1 Jeneponto di era media sosial. Di tengah tekanan psikologis akibat disrupsi arus digital, pembelajaran yang mengintegrasikan teknologi dan nilai budaya menjadi semakin relevan. Analisis penelitian ini menggunakan Teori Pedagogi Tanggap Budaya (Culturally Responsive Pedagogy) dari Geneva Gay yang menyatakan bahwa identitas dan kearifan kultural siswa merupakan aset kekuatan yang mampu menjadi jangkar pelindung emosional mereka. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan mengeksplorasi praktik pembelajaran digital berbasis nilai lokal. Keabsahan data diuji melalui triangulasi sumber, triangulasi metode, dan member checking untuk memastikan kredibilitas serta ketepatan interpretasi hasil penelitian. Hasil penelitian menunjukkan bahwa CRDL berkontribusi signifikan melalui lima aspek. Pertama, pembelajaran berbasis karya digital seperti vlog dan podcast meningkatkan kepercayaan diri siswa dengan mendorong mereka bertransformasi menjadi kreator yang berdaya. Kedua, internalisasi nilai tata krama budaya membentuk perilaku bijak bermedia sosial. Ketiga, penguatan esensi nilai diri membantu siswa agar tidak bergantung pada validasi digital yang semu, seperti likes dan followers. Keempat, tugas berbasis interaksi keluarga mempererat hubungan emosional, menjadikan keluarga sebagai sumber dukungan utama dan tempat bersandar yang hangat. Kelima, pembelajaran berbasis keberagaman budaya terbukti efektif dalam mencegah cyberbullying.